2011
DOI: 10.1007/s00540-011-1257-6
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine treatment during synapse reformation periods permanently inhibits NGF-induced excitation in an identified reconstructed synapse of Lymnaea stagnalis

Abstract: NGF increased amplitudes and frequencies of MEPPs and induced synaptic excitation by increasing axonal growth and exocytosis. Lidocaine exposure during synapse reformation periods permanently suppressed NGF-induced excitation by suppressing axonal growth and exocytosis of presynaptic neurons in the identified reconstructed synapse of L. stagnalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…Our results demonstrated that the synaptic responses (EPSPs) had higher sensitivity to neonicotinoids and the inhibition was less reversible compared to the membrane responses (depolarization) evoked by ACh on the same follower, RPeD1 (as seen on (Onizuka et al, 2012). These results confirm a potential functional heterogeneity, in terms of different sensitivities or coupling mechanisms, of the nACh receptors which are located synaptically versus extrasynaptically on the same neuron.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our results demonstrated that the synaptic responses (EPSPs) had higher sensitivity to neonicotinoids and the inhibition was less reversible compared to the membrane responses (depolarization) evoked by ACh on the same follower, RPeD1 (as seen on (Onizuka et al, 2012). These results confirm a potential functional heterogeneity, in terms of different sensitivities or coupling mechanisms, of the nACh receptors which are located synaptically versus extrasynaptically on the same neuron.…”
Section: Discussionsupporting
confidence: 75%
“…Both connections have also been shown to re-form between the isolated neurons when placed in culture conditions (Syed et al, 1990;Hamakawa et al, 1999). The first, excitatory component of these monosynaptic connections provides a suitable in vitro model while studying synaptogenesis (Feng et al, 1997;Woodin et al, 2002), or toxin-induced alterations of cholinergic neurotransmission (Woodall et al, 2003;Onizuka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The following are examples of the main types of research conducted using cultured neuronal cells. (1) identification and functional characterization of neurotrophic factors regulating neurite outgrowth and regeneration (Spence et al 1998; Goldberg 1998; Munno et al 2000; Dmetrichuk et al 2008; Milanese et al 2009; Nejatbakhsh et al 2011 and others ), (2) growth cone motility and development (Spencer et al 1998; Dmetrichuk et al 2008; Suter 2011), (3) neurite-soma and soma-soma synaptogenesis (Munno et al 2000; Hu et al 2004; Onizuka et al 2012) and (4) neuronal receptors and cell-to-cell neurotransmitter signaling (White and Laczmarek 1997; Mapara et al 2008; Giachello et al 2010; Ye et al 2010). …”
Section: Molluscan Primary Cell Culturesmentioning
confidence: 99%
“…Its actions can be accounted for by assuming that procaine binds preferentially to the activated receptor-channel complex and converts it into a non-conducting state (Ascher et al, 1976; Marty, 1978). In Achatina fulica (Ferussac), procaine initiated paroxysmal depolarizing shifts (PDSs) in the RP1 neuron, which were decreased if lithium replaced Na + in the bathing medium or in a high magnesium solution (Lin and Tsai, 2005), suggesting similar effects to those observed with lidocaine by Onizuka et al (2012a) (see above). In addition, PDS was associated with phospholipase activity and calcium mobilization in the neuron (Lin et al, 2010).…”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 81%
“…By pairing VD4 with neurons from the left pedal E (LPeE) cluster it has also been possible to show that lidocaine treatment during synapse formation permanently suppresses nerve growth factor (NGF) induced excitation by suppressing both axonal growth and neurotransmitter release from presynaptic neurons (Onizuka et al, 2012a) probably by suppressing voltage-dependent calcium currents (Kasaba et al, 2006). …”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%